Identification of the "Collagen-Macrophage" sub-category of patients with colorectal cancer as an extension of the CMS4 subtype with THBS2 as a therapeutic target - Shuwen Chen; Zhaoyan Jiang; Wanxuan Song; Chuqiao Lu; Yanbing Lin; Shiyao Xu; Kunxin Xie; Li Wan; Xiaoqin Yuan (BMC Gastroenterology)
Abstract We identified a subset of patients with colorectal cancer (CRC) enriched with “collagen-TAMs,” designated the CM class, using large integrated colon cancer transcriptome and single-cell transcriptome datasets. This classification system could be used as an extension of the traditional CMS classification system for CRC to guide more accurate classification and treatment. We also screened CAF-derived THBS2 as a potential biomarker for CM and found that it plays an important role in CRC disease models in vitro and in vivo, promoting tumor development and metastasis as well as TAM recruitment. Targeting THBS2 combined with PD-1 therapy effectively improved the therapeutic effect of immunotherapy in vivo. The CM classification provides a new perspective for CRC treatment, and THBS2, which is highly expressed in CM cases, can be used as a new potential combined target for immunotherapy.